Child growth and refugee status: Evidence from Syrian migrants in Turkey - Murat Demirci; Andrew D. Foster; Murat G. Kirdar (Koç University-TÜSIAD Economic Research Forum (ERF), 2022)
This study examines disparities in health and nutrition among native and Syrian-refugee children in Turkey. With a view toward understanding the need for targeted programs addressing child well-being among the refugee population, we analyze, in particular, the Turkey Demographic and Health Survey (TDHS). The TDHS is one of few data sets providing representative data on health and nutrition for a large refugee and native population. We find no evidence of a difference in infant or child mortality between refugee children born in Turkey and native children. However, refugee infants born in Turkey have lower birthweight and ageadjusted weight and height than native infants. When we account for a rich set of birth and socioeconomic characteristics that display substantial differences between natives and refugees, the gaps in birthweight and age-adjusted height persist, but the gap in age-adjusted weight disappears. Although refugee infants close the weight gap at the mean over time, the gap at the lower end of the distribution persists. The rich set of covariates we use explains about 35% of the baseline difference in birthweight and more than half of the baseline difference in current height. However, even after that, refugee infants' average birthweight is 0.17 standard deviations (sd) lower and their current height is 0.23 sd lower. These gaps are even larger for refugee infants born prior to migrating to Turkey, suggesting that remaining deficits reflect conditions in the source country prior to migration rather than deficits in access to maternal and child health services within Turkey.
Keywords: J61; O15; F22; R23; R58; 330; Syrian refugees; birthweight; anthropometric measures; forced displacement; Turkey